Generalization of Rubel’s result for operators - Linchuk, Yu. S. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
We describe all pairs of linear continuous operators that act in spaces of functions analytic in domains and satisfy a relation that is an operator analog of the Rubel equation.